Study of Relationship between Fingerprint Patterns and Gender among the Assamese Population of Barpeta - Jayasri Devi, Santanu Kumar Sarma, Tribeni Medhi, Priyankita Nath (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Universally accepted tool for identification of an individual is fingerprint. Scientific analysis  of  fingerprints, lines, mounts and shape of the hands called ‘dermatoglyphics’. There are three primary patterns of fingerprint viz., loops, whorls and arches which are unique in each individual and extensively used in forensic medicine as well as in biometrics. Fingerprints are affected by multiple factors including hereditary, environmental and regional.